Distinct Dynamics of Stem and Progenitor Cells in Blood of Polytraumatized Patients. Issue 4 (April 2019) - Vogel, Mona; Christow, Hannes; Manz, Isabel; Denkinger, Michael; Amoah, Amanda; Schütz, Desiree; Brown, Andreas; Möhrle, Bettina; Schaffer, Annika; Kalbitz, Miriam; Gebhard, Florian; Mayer, Benjamin; et al.
Abstract : ABSTRACT: Endogenously mobilized stem and progenitor cells (SPCs) or exogenously provided SPCs are thought to be beneficial for trauma therapy. However, still little is known about the synchronized dynamics of the number of SPCs in blood after severe injury and parameters like cytokine profiles that correlate with these numbers. We determined the number of hematopoietic stem cells, common myeloid progenitors, granulocyte-macrophage progenitors, and mesenchymal stem/stromal cells in peripheral blood (PB) 0 to 3, 8, 24, 48, and 120 h after polytrauma in individual patients (injury severity score ≥ 21). We found that the number of blood SPCs follows on average a synchronous, inverse bell-shaped distribution, with an increase at 0 to 3 h, followed by a strong decrease, with a nadir in SPC numbers in blood at 24 or 48 h. The change in numbers of SPCs in PB between 48 h and 120 h revealed two distinct patterns: Pattern 1 is characterized by an increase in the number of SPCs to a level higher than normal, pattern 2 is characterized by an almost absent increase in the number of SPCs compared to the nadir. Changes in the concentrations of the cytokines CK, MDC, IL-8, G-CSF Gro-α, VEGF, and MCP-1 correlated with changes in the number of SPCs in PB or were closely associated with Pattern 1 or Pattern 2. Our data provide novel rationale for investigations on the role of stem cell mobilization in polytraumatized patients and its likely positive impact on trauma outcome. Abstract : Supplemental Digital Content is available in the text